Characteristics and Absorption Coefficient of Co2 Laser in Natural Gas Mixtures - Mohd Saad, Norhafidzah (2006)
This work was arranged to develop scientific and engineering database on the study of cw / repetitively pulsed CO2 laser in terms of its characteristics and absorption coefficient in natural gas mixtures. The laser system is operated both in continuous wave mode as well as in pulse mode at 10.6µm wavelength range of infrared electromagnetic spectrum.